(3GdJjSjQ aj GdJaSjQs - (3GdfSaj, CHh MaU, fLe GdOjf, YeQ Hf eMeO CMeO, J (B537 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj CfRd GdbQBf TaGA hQMeI bGd GdYHO GdVYja YeQ Hf eMeO Hf GMeO GdfSaj aCbhd ddfGS aj eYfi GdJaSjQ hGdJChjd Hjf GdJbUjQ hGdJWhjd hdfG Ydi GdJhSW JYhjds
(3BNQgG (B:s
(3bGd ef bQC ShQI GdeGFOI TaY dg YjSi Ydjg GdSdGe hCYWj eKd CLQ MhGQj YjSi Ydjg GdSdGe hcJH dg Hcd BjI bQCgG eKd KhGH YeGQ HjJ GdebOS hGdMeO ddg QH GdYGdejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5 / 60s
(3eYLe GdeDdajf (B2 / 571s
(3cTa GdXfhf (B1 / 519s
(3TPQGJ GdPgH (B4 / 115s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs